2017
DOI: 10.1002/anie.201611351
|View full text |Cite
|
Sign up to set email alerts
|

The Parent Cyclopentadienyltin Cation, Its Toluene Adduct, and the Quadruple‐Decker [Sn3Cp4]2+

Abstract: Truly cationic metallocenes with the parent cyclopentadienyl ligand are so far unknown for the Group 14 elements. Herein we report on an almost "naked" [SnCp] cation with the weakly coordinating [Al{OC(CF ) } ] and [{(F C) CO} Al-F-Al{OC(CF ) } ] anions. [SnCp][Al{OC(CF ) } ] was used to prepare the first main-group quadruple-decker cation [Sn Cp ] again as the [Al{OC(CF ) } ] salt. Additionally, the toluene adduct [CpSn(C H )][Al{OC(CF ) } ] was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 31 publications
4
30
0
1
Order By: Relevance
“…[276] Furthermore,it has subsequently been demonstrated that the reaction of Si(C 5 Me 5 ) 2 with the Brønsted acid [H(OEt 2 ) 2 ][Al(OR F ) 4 ] results in the formation of [Si(C 5 Me 5 )] + supported by the [Al(OR F ) 4 ] À ion. [362] Subvalent 4 ]c omplexes readily bind s-donor ligands (e.g. Thecation is formed through either halide abstraction from CpSnCl by Ag[Al(OR F ) 4 ], or by Cp abstraction from Cp 2 Sn by Me 3 SiF-Al(OR F ) 3 .F urthermore,t he reaction of [CpSn] + with Cp 2 Sn results in the formation of the quadruple decker complex in which [CpSn] + cations are attached to either end of the "neutral" Cp 2 Sn in abent cisoid arrangement.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…[276] Furthermore,it has subsequently been demonstrated that the reaction of Si(C 5 Me 5 ) 2 with the Brønsted acid [H(OEt 2 ) 2 ][Al(OR F ) 4 ] results in the formation of [Si(C 5 Me 5 )] + supported by the [Al(OR F ) 4 ] À ion. [362] Subvalent 4 ]c omplexes readily bind s-donor ligands (e.g. Thecation is formed through either halide abstraction from CpSnCl by Ag[Al(OR F ) 4 ], or by Cp abstraction from Cp 2 Sn by Me 3 SiF-Al(OR F ) 3 .F urthermore,t he reaction of [CpSn] + with Cp 2 Sn results in the formation of the quadruple decker complex in which [CpSn] + cations are attached to either end of the "neutral" Cp 2 Sn in abent cisoid arrangement.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thecation is formed through either halide abstraction from CpSnCl by Ag[Al(OR F ) 4 ], or by Cp abstraction from Cp 2 Sn by Me 3 SiF-Al(OR F ) 3 .F urthermore,t he reaction of [CpSn] + with Cp 2 Sn results in the formation of the quadruple decker complex in which [CpSn] + cations are attached to either end of the "neutral" Cp 2 Sn in abent cisoid arrangement. [362] Subvalent [M(arene) n ] + Complex Cations (M = Ga, In): An elegant entry into low oxidation state Group 13 chemistry is the direct oxidation of gallium or indium metal by the silver salt Ag[Al(OR F ) 4 ]i na romatic solvents.T he resulting [E-(arene) n ][Al(OR F ) 4 ]c omplexes readily bind s-donor ligands (e.g. PPh 3 or P t Bu 3 )t of orm the pyramidal [Ga(PPh 3 ) 3 ] + cation, and with the more sterically demanding P t Bu 3 to form the cationic carbene analogue [Ga(P t Bu 3 ) 2 ] + .…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Ad istinction between neutral and cationic Lewisa cids has to be emphasized. Computed FIAs for beryllium, [56] borenium, [57] carbenium, [58] silylium, [38a, 59] phosphenium, [60] phosphonium, [61] zinc, [62] or other cationic species [63] exceed the threshold to LSA significantly.T he FIA of ac ationic compoundi nt he gas phase is strongly increased by charge neutralization and by electrostatic attraction. However,adamping of the FIA by the enthalpy of solvation (DH solv )i sm uch more pronounced for charged( cationic) than for neutral acids (Figure 4b).…”
Section: Cn Stretching Mode Of Acetonitrile Adductsmentioning
confidence: 99%
“…By using the Lewis acid Me 3 SiF-Al(OC(CF 3 ) 3 ) 3 ,t he fluoride-bridged anion (CF 3 ) 3 CO) 3 Al-F-Al(OC(CF 3 ) 3 ) 3 can easily be introduced as ("the least")w eakly coordinating anion. [27,63,123] The reaction of two Al(OC(CF 3 ) 3 ) 3 with one F À reveals an incomparably high FIA of 685 kJ mol À1 . [124] Al(C 6 F 5 ) 3 (FIA [29] 536 kJ mol À1 ): Al(C 6 F 5 ) 3 is one of the most extensively used Lewis superacids.…”
Section: Ageneral Classification Of Scalingm Ethodsmentioning
confidence: 99%
See 1 more Smart Citation